2022
DOI: 10.3390/diseases10030039
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Nickel Levels Correlate with Low Muscular Strength and Renal Function Parameters in Patients with Prostate Cancer

Abstract: Nickel is associated with cancer in occupational exposure. However, few studies have been devoted to analyzing the effects of nickel at environmental concentrations in cancer patients. In this work, the concentration of nickel in blood samples from patients with prostate cancer (PCa) was evaluated because this metal displays androgenic and estrogenic effects that play a crucial role in prostate carcinogenesis and treatment. We, therefore, compared blood nickel concentration in patients with PCa (non-occupation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…After adjusted for some confounding factors, we also found that for every 1ug/L increase in blood nickel level, the patient’s HGS decreases by 2.81 kg. Our results were in accordance with previous study [ 20 ], which showed significant associations between plasma nickel level and HGS in other population.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…After adjusted for some confounding factors, we also found that for every 1ug/L increase in blood nickel level, the patient’s HGS decreases by 2.81 kg. Our results were in accordance with previous study [ 20 ], which showed significant associations between plasma nickel level and HGS in other population.…”
Section: Discussionsupporting
confidence: 94%
“…Noteworthily, previous animal researchers found that nickel could affect muscle development [ 18 , 19 ]. In addition, a recent study reported that plasma nickel level correlated with low muscular strength measured with the handgrip test in non-dialysis patients, thus suggesting a possible link between these two parameters [ 20 ]. Nevertheless, to the best of our knowledge, association between blood nickel and HGS in patients undergoing MHD has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%